Preparation and Diagnosis of Polyethylene terephthalate (PET) And Studying of Its Effect as Additives on the Concrete Properties - Bachari, Thamir Salman (Basrah Journal for Engineering Sciences, 2013)
Polyethylene terephthalate (PET) was prepared from (PET) flakes and 25% of NaOH solution were added to in tri-neck flask, the reaction run for six hours at temperature (100-130) oC and the precipitate was reacted with ethylene glycol at temperature (130-160) oC. IR spectrophotometer was used for the diagnoses of (PET). Differential scanning calorimeter (DSC) is used to indicate glass transition temperature Tg, the melting temperature Tm and the heat absorbed. Part hundred ratios (phr,s) of (PET) rather than dosage of PET in gms. To concrete cubes were added to study its effect on concrete properties. Additives of (phr,s) impart performance such as increased cement dispersion, and enhance the performance of concrete which was appeared in maintaining a lengthening or slow the setting time that meets product and job needs. Maximum and minimum compressive strength is 43.7 MPa and 30.0 MPa at 0.3 gm. and 0.1 gm. respectively.